2023
DOI: 10.3390/biology12010109
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Response of Metabolic Activity of an Antarctic Nematode

Abstract: Because of climate change, the McMurdo Dry Valleys of Antarctica (MCM) have experienced an increase in the frequency and magnitude of summer pulse warming and surface ice and snow melting events. In response to these environmental changes, some nematode species in the MCM have experienced steady population declines over the last three decades, but Plectus murrayi, a mesophilic nematode species, has responded with a steady increase in range and abundance. To determine how P. murrayi responds to increasing tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…However, as the temperature approached the upper limits, nematode sensitivity to plant compounds of E. adenophorum. The increase in metabolic temperature, on the one hand, and the increase in the release rate of compounds to the soil at higher temperatures can reason for the increase in mortality in the nematode [44].…”
Section: Discussionmentioning
confidence: 99%
“…However, as the temperature approached the upper limits, nematode sensitivity to plant compounds of E. adenophorum. The increase in metabolic temperature, on the one hand, and the increase in the release rate of compounds to the soil at higher temperatures can reason for the increase in mortality in the nematode [44].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, high temperature has been found to cause sex reversal from female to male (which are non-parasitic in nature) in the parthenogenetic root-knot nematodes ( Papadopoulou and Triantaphyllou, 1982 ). A recent study with Antarctic population of free-living nematode Plectus murrayi showed that rise in temperature increases the metabolic activities and O 2 consumption thereby disrupting the ecosystem structure and function ( Robinson et al., 2023 ). The authors, in context of carbon-limited soil ecosystem of polar habitat, speculated higher nematode abundance in deeper soil due to vertical range expansion.…”
Section: Effect Of Global Climate Change On Plant-parasitic Nematodesmentioning
confidence: 99%